Longitudinal changes in amyloid positron emission tomography and volumetric magnetic resonance imaging in the nondemented Down syndrome population. Issue 1 (23rd May 2017) - Lao, Patrick J.; Handen, Ben L.; Betthauser, Tobey J.; Mihaila, Iulia; Hartley, Sigan L.; Cohen, Annie D.; Tudorascu, Dana L.; Bulova, Peter D.; Lopresti, Brian J.; Tumuluru, Rameshwari V.; Murali, Dhanabalan; Mathis, Chester A.; et al.
Abstract: Introduction: Down syndrome (DS) arises from a triplication of chromosome 21, causing overproduction of the amyloid precursor protein and predisposes individuals to early Alzheimer's disease (AD). Methods: Fifty‐two nondemented adults with DS underwent two cycles of carbon 11‐labeled Pittsburgh compound B ([ 11 C]PiB) and T1 weighted magnetic resonance imaging (MRI) scans 3.0 ± 0.6 years apart. Standard uptake value ratio (SUVR) images (50–70 minutes; cerebellar gray matter [GM]) and GM volumes were analyzed in standardized space (Montreal Neurological Institute space). Results: 85% of PiB(−) subjects remained PiB(−), whereas 15% converted to PiB(+), predominantly in the striatum. None reverted from PiB(+) to PiB(−). Increases in SUVR were distributed globally, but there were no decreases in GM volume. The PiB positivity groups differed in the percent rate of change in SUVR [PiB(−): 0.5%/year, PiB converters: 4.9%/year, and PiB(+): 3.7%/year], but not in GM volume. Discussion: Despite the characteristic striatum‐first pattern, the global rate of amyloid accumulation differs by pre‐existing amyloid burden and precedes atrophy or dementia in the DS population, similar to general AD progression.